Finite element modelling to predict the flexural behaviour of ultra-high performance concrete members. (15th March 2019) - Yin, Hor; Shirai, Kazutaka; Teo, Wee
Highlights: An FE model for predicting the flexural behaviour of UHPC was investigated. The numerical approach was validated with 21 UHPC specimens. The FE model accurately traces the flexural performance of the tested specimens. The simulated and experimental ultimate load and deflection agree well. Abstract: This paper presents a finite element (FE) modelling to predict the behaviour of ultra-high performance concrete (UHPC) members under static flexural loading. A plasticity-based constitutive model for concrete and an implicit solver in LS-DYNA were adopted in the numerical simulation. Experimental data for 21 UHPC specimens tested in the present study and in previous works were used to calibrate and validate the proposed FE model and modelling technique. The simulation was able to accurately predict the experimentally obtained ultimate strength, stiffness, and hardening and softening behaviours of the specimens. This demonstrates the effectiveness and adequacy of the developed FE model and modelling technique.